Revisiting long-run dynamics of the determinants of public education expenditure in Malaysia - Wong Sing Yun; Remali Yusoff (Penerbit UMS, 2018)
This main purpose of this paper is to revisit the long run dynamics on Malaysia's public education expenditure determinants during the period of 1982 to 2016. This study will also attempt to discuss some of the relevant theories that are able to explain and characterized the pattern of Malaysia's public education expenditure. A relatively recent developed estimation technique, ARDL bound testing was employed to estimate the long run relationship between public education expenditure and its determinants. The results based on the ARDL bound testing approach concluded that a stable, long-run co-integrated relationship exists between public education expenditure and its determinants: real gross domestic product (GDP), unemployment rate (UNEM), inflation rate (INF) and working age population (POP2). Furthermore, the result highlighted the relevance and suitability of Keynesian Counter Cyclical theory, Economic-Demography theory and Peacock-Wiseman in explaining the pattern of Malaysia's public education expenditure. In addition, bilateral causality was found between public education expenditure and real GDP. Similarly, a two-way causal relationship was also found between tax revenue and public education spending. Finally, this study suggests that policymakers should pay more attention to the economic situations and the demands from society when formulating future policies or allocations.